Bimbingan Kelompok dalam Mengelola Stres Akademik Santri Tahfizh - Sulistiana Sulistiana; Nur Hermatasiyah; Aceng Akhmad Munandzar Alkafi Billah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to describe the forms of academic stress, identify the causing factors, and understand the role of group guidance services in helping tahfizh students manage stress at Pesantren Riyadhul Qur’an Ar Ridwan. The method used is a qualitative approach with a descriptive research type. Data collection was carried out through field observation, in-depth interviews with seven research subjects, and documentation studies. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that students experience academic stress due to dual demands between Al-Qur’an memorization targets and the academic curriculum, manifesting as anxiety, physical fatigue (headaches), and procrastination. The implementation of group guidance services through Prayitno’s four systematic stages (formation, transition, activity, and termination) proved to play an important role as a curative and preventive solution. Through group dynamics, students are able to restructure their mindsets to change negative perceptions of the memorization burden into positive challenges and improve time management skills. Emotional support and a sense of solidarity built between group members significantly help reduce students' psychological burdens. In conclusion, group guidance is an effective strategy to improve psychological well-being and significantly reduce the level of academic stress for tahfizh students.